2021
DOI: 10.3233/npm-200409
|View full text |Cite
|
Sign up to set email alerts
|

Bedside sonography performed by neonatology residents to confirm central vascular catheter position in neonates – A Prospective Diagnostic Evaluation study

Abstract: OBJECTIVE: To evaluate the diagnostic accuracy and utility of bedside ultrasound (US) by neonatology residents to confirm position of umbilical venous catheter (UVC), umbilical arterial catheter (UAC), and peripherally inserted central catheter (PICC). METHODS: In this prospective study, we included neonates who required UVC, UAC or PICC insertion. Two neonatology residents performed all bedside US examinations after a short period of training. Plain radiograph was taken as gold standard. Time taken for confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Anatomical survey with transverse, sagittal and cine images of trachea, thymus, lungs and pleura, great vessels, aortic arch, heart. Dedicated transverse and sagittal views of the tip and shaft of the PICC Neonatology resident with 4 years’ experience in US or attending radiologist with subspecialisation in sonography (~ 30 years) Shabeer et al [ 40 ] 13-MHz linear probe. Right parasternal axis and subcostal views 2 neonatology residents with 18 months of neonatal training and who perform regular US examinations of the brain and heart Telang et al [ 37 ] 5–12 MHz sector probe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical survey with transverse, sagittal and cine images of trachea, thymus, lungs and pleura, great vessels, aortic arch, heart. Dedicated transverse and sagittal views of the tip and shaft of the PICC Neonatology resident with 4 years’ experience in US or attending radiologist with subspecialisation in sonography (~ 30 years) Shabeer et al [ 40 ] 13-MHz linear probe. Right parasternal axis and subcostal views 2 neonatology residents with 18 months of neonatal training and who perform regular US examinations of the brain and heart Telang et al [ 37 ] 5–12 MHz sector probe.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies documented that the reference test was reported incorrectly. These erroneous radiographic reports were ultimately corrected following the US examination, which demonstrated a more accurate tip position [ 36 , 38 40 ]. Radiographic misinterpretations in these four studies were a mixture of false reports of malposition and false reports of optimum position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ultrasound performed by neonatal residents and neonatal nurse practitioners has good results in terms of diagnostic accuracy, after adequate training ( 49 , 50 ).…”
Section: Insertion Of the Uvc Including New Technologiesmentioning
confidence: 99%
“…7 Aside from PCVCs, confirming the location of the tips of other catheters, including umbilical vein and umbilical artery catheters used commonly in premature babies, was also reported. 8 However, due to the small number of cases requiring this procedure, the evidence is insufficient for supporting the use of US as the gold-standard tool for identifying the tip location of PCVCs.…”
Section: Introductionmentioning
confidence: 99%